2022
DOI: 10.31258/unricsce.3.673-679
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi stunting pada anak balita di Desa Rantau Mapesai

Abstract: Stunting is a condition of failure to thrive in children due to malnutrition for a long time. Thus, the child is shorter than normal children his age and has a delay in thinking. Generally caused by food intake that is not in accordance with nutritional needs. Stunting is a major nutritional problem in Indonesia. Stunting can be caused by lack of nutritious food intake, exclusive breastfeeding, low birth weight, and a history of infection. Stunting can have an impact on motor and verbal development, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many mothers and children still do not attend posyandu, so health workers and posyandu cadres consistently visit and monitor the development of stunted children in their homes. This approach aligns with the findings of Fauza et al (2022), who identified factors contributing to stunting, including limited access to nutritious food, insufficient intake of vitamins and minerals, and a lack of dietary diversity and animal protein sources. Additionally, suboptimal maternal care practices, particularly regarding child feeding behaviors and nutritional intake, were identified as factors contributing to child stunting.…”
Section: Interview With Mrs Lukluatun (Mch Midwife)mentioning
confidence: 56%
“…Many mothers and children still do not attend posyandu, so health workers and posyandu cadres consistently visit and monitor the development of stunted children in their homes. This approach aligns with the findings of Fauza et al (2022), who identified factors contributing to stunting, including limited access to nutritious food, insufficient intake of vitamins and minerals, and a lack of dietary diversity and animal protein sources. Additionally, suboptimal maternal care practices, particularly regarding child feeding behaviors and nutritional intake, were identified as factors contributing to child stunting.…”
Section: Interview With Mrs Lukluatun (Mch Midwife)mentioning
confidence: 56%